2016
DOI: 10.1186/s11671-016-1481-y
|View full text |Cite
|
Sign up to set email alerts
|

The Fabrication of Nanoimprinted P3HT Nanograting by Patterned ETFE Mold at Room Temperature and Its Application for Solar Cell

Abstract: Nanoimprinting lithography (NIL) is investigated as a promising method to define nanostructure; however, finding a practical method to achieve large area patterning of conjugated polymer remains a challenge. We demonstrate here that a simple and cost-effective technique is proposed to fabricate the nanoimprinted P3HT nanograting by solvent-assisted room temperature NIL (SART-NIL) method with patterned ETFE film as mold. The patterned ETFE template is produced by embossing ETFE film into a patterned silicon mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It was reported that the NIL technique was not only able to fabricate the nanostructures but also to induce transition of the molecular and crystallographic ordering of imprinted materials which were able to self-organize. [30][31][32][33][34][35][36] In order to probe the effect of the VART-NIL procedure on the molecular alignment of P3HT polymer molecule, GIWAXD measurements of the polymer P3HT lm before and aer patterning were performed, with the corresponding results shown in Fig. 3 and 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that the NIL technique was not only able to fabricate the nanostructures but also to induce transition of the molecular and crystallographic ordering of imprinted materials which were able to self-organize. [30][31][32][33][34][35][36] In order to probe the effect of the VART-NIL procedure on the molecular alignment of P3HT polymer molecule, GIWAXD measurements of the polymer P3HT lm before and aer patterning were performed, with the corresponding results shown in Fig. 3 and 4.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we also adopted the standard crystallographic notation for the P3HT polymer, where the (h00) plane, (010) plane and (001) plane are referred to as the layering direction, p-p direction and backbone direction, respectively. [30][31][32][33][34][35][36] Fig. S3 in the ESI † shows two typical edge-on and face-on molecule alignments of P3HT molecule chains on the substrate surface, and the lattice parameters a, b and c are distances between the backbones, p-p stacking distance and distance between the side chains, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Recently, our group has presented a simple and cost-effective solvent-assisted room-temperature NIL (SART-NIL) method based on the NIL technique to fabricate the polymer nanostructure or induce the molecular alignment. [30][31][32][33] However, a comprehensive understanding of the NIL process in dening or reorienting the molecular alignment is unclear and the simultaneous determination of the polymer chain alignment and nanostructure morphology still has a long way to go.…”
Section: Introductionmentioning
confidence: 99%